Pengaruh Financial Distress terhadap Opini Audit Going Concern: (Emiten Properties dan Real Estate di Bursa Efek Indonesia Periode 2019-2023) - Najwa Balqis; Sumarno Manrejo; Bambang Prayogo (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The purpose of this study was to test and analyze the effect of financial distress on going concern audit opinion. This research method uses quantitative research methods, with the type and source of data, namely secondary data. The population and sample of this study are properties & real estate companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling technique and resulted in 110 samples of processed data that met the criteria. The analysis method used is descriptive statistical analysis, logistic regression analysis, and hypothesis testing. The results of this study indicate partially that financial distress has a positive effect on going concern audit opinion.